Fibre elongation requires normal redox homeostasis modulated by cytosolic ascorbate peroxidase in cotton (Gossypium hirsutum) - Guo, Kai (Journal of experimental botany, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the Society for Experimental Biology.